2017
DOI: 10.3847/1538-4357/aa8df4
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Lyα Emission around a z ∼ 6.6 QSO with MUSE: Extended Emission and a Companion at a Close Separation

Abstract: We utilize the Multi Unit Spectroscopic Explorer (MUSE) on the Very Large Telescope to search for extended Lyα emission around the z∼6.6 QSO J0305−3150. After carefully subtracting the point spread function, we reach a nominal 5σ surface-brightness limit of SB 5σ =1.9×10−18 ergs −1 cm −2 arcsec −2 over a 1arcsec 2 aperture, collapsing fivewavelength slices centered at the expected location of the redshifted Lyα emission (i.e., at 9256 Å). Current data suggest the presence (5σ accounting for systemat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
71
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 166 publications
5
71
1
Order By: Relevance
“…an order of magnitude higher, and likewise, J1030+0524, which previously was not reported to display a Lyα halo, now appears with a small halo of moderate luminosity, that is an order of magnitude more luminous than Farina et al (2017). This stresses the need for larger samples of Lyα halos around QSOs at z ∼ 6.…”
Section: Evidence For Luminosity Evolution?mentioning
confidence: 67%
See 4 more Smart Citations
“…an order of magnitude higher, and likewise, J1030+0524, which previously was not reported to display a Lyα halo, now appears with a small halo of moderate luminosity, that is an order of magnitude more luminous than Farina et al (2017). This stresses the need for larger samples of Lyα halos around QSOs at z ∼ 6.…”
Section: Evidence For Luminosity Evolution?mentioning
confidence: 67%
“…Using the quasar itself allows us to avoid issues related to PSF variations across the field, and spatial interpolation. Indeed, in the analysis of the z ∼ 6 quasar presented in Farina et al (2017), these two commonly-applied PSF subtraction techniques were tested, and found to be equally reliable.…”
Section: Psf Subtractionmentioning
confidence: 99%
See 3 more Smart Citations